2015
DOI: 10.1038/nrdp.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) occurs in 5-10% of the population and is twice as common in women as in men. Although trauma exposure is the precipitating event for PTSD to develop, biological and psychosocial risk factors are increasingly viewed as predictors of symptom onset, severity and chronicity. PTSD affects multiple biological systems, such as brain circuitry and neurochemistry, and cellular, immune, endocrine and metabolic function. Treatment approaches involve a combination of medications and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
610
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 673 publications
(646 citation statements)
references
References 230 publications
19
610
0
17
Order By: Relevance
“…In relation to avoidance and numbing PTSS clusters in adults, functional imaging studies reported negative correlation with activation in dorsomedial prefrontal cortex (Frewen et al, 2012) and rostral anterior and subcallosal cingulate regions, in conjunction with positive correlation with superior temporal cortex activation (Hopper et al, 2007). These findings are consistent with an emotion dysregulation model positing post-traumatic alteration in pathway integrity and network connectivity of structures involved in top-down inhibition of limbic structures that regulate emotional reactivity (Yehuda et al, 2015). High levels of noradrenergic signaling may contribute to emotion dysregulation through inhibition of prefrontal regulatory systems, resulting in increased activity and reactivity in the amygdala (Hendrickson and Raskind, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…In relation to avoidance and numbing PTSS clusters in adults, functional imaging studies reported negative correlation with activation in dorsomedial prefrontal cortex (Frewen et al, 2012) and rostral anterior and subcallosal cingulate regions, in conjunction with positive correlation with superior temporal cortex activation (Hopper et al, 2007). These findings are consistent with an emotion dysregulation model positing post-traumatic alteration in pathway integrity and network connectivity of structures involved in top-down inhibition of limbic structures that regulate emotional reactivity (Yehuda et al, 2015). High levels of noradrenergic signaling may contribute to emotion dysregulation through inhibition of prefrontal regulatory systems, resulting in increased activity and reactivity in the amygdala (Hendrickson and Raskind, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Although numerous changes in HPA-axis (re)activity have been observed in PTSD, some of the findings have not followed those described as part of classic acute or chronic responses to challenge. GC alterations in PTSD [recently reviewed in: (Yehuda et al, 2015d)] involve: Altered adrenal production of GCs. PTSD has been mostly associated with lower levels of the stress hormone cortisol (Yehuda et al, 2015d).…”
Section: Glucocorticoids (Gcs) and Peripheral Inflammation In Ptsdmentioning
confidence: 99%
“…GC alterations in PTSD [recently reviewed in: (Yehuda et al, 2015d)] involve:

Altered adrenal production of GCs. PTSD has been mostly associated with lower levels of the stress hormone cortisol (Yehuda et al, 2015d). However, some studies failed to observe differences in the basal GC tone and others reported increased basal cortisol levels (Klaassens et al, 2012; Meewisse et al, 2007; Morris et al, 2012).

…”
Section: Glucocorticoids (Gcs) and Peripheral Inflammation In Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been recent reviews of PTSD that have included a discussion of the functional neuroimaging literature 12 and several recent reviews of the microcircuitry involved in brain regions implicated in PTSD-related circuits 7,8,10 , there has not yet been an attempt to bridge human and animal literatures in the discussion of PTSD pathophysiology. Because the DSM-5 remains dominant in clinical academic medicine, we have chosen to structure this Review according to its criteria rather than the categories outlined in the RDoC; however, we provide an attempt to align the DSM-5 criteria with the current RDoC matrix (TABLE 1).…”
mentioning
confidence: 99%